2015
DOI: 10.3126/jucms.v3i1.13256
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Refractive Error in Primary School Children in Rupandehi District, Nepal

Abstract: INTRODUCTION: Refractive error remains one of the primary causes of visual impairment in children worldwide. This study describes pattern of refractive errors among primary school students in Rupandehi district, Nepal.MATERIAL AND METHODS: Records of 128 children with refractive error aged 5-15 years from both urban and rural areas in Nepal between January and March 2011 were examined for patterns in the distribution of refractive errors. SPSS statistical software was used to perform analysis.RESULTS: The comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This is comparable with the study of Rai et al 9 Pavithra et al 4 and Matta S et al 8 observed myopia to be the most common refractive error. Medi et al 10 showed commonest refractive error was astigmatism (52%) followed by hypermetropia (37%) and least common was myopia (11%).…”
Section: Discussionsupporting
confidence: 82%
“…This is comparable with the study of Rai et al 9 Pavithra et al 4 and Matta S et al 8 observed myopia to be the most common refractive error. Medi et al 10 showed commonest refractive error was astigmatism (52%) followed by hypermetropia (37%) and least common was myopia (11%).…”
Section: Discussionsupporting
confidence: 82%
“…Myopia was the most common refractive error (31.1%) followed by astigmatism (29.4%), and hyperopia (2.6%) being the least and many studies have reported similar results. [ 8 13 20 21 22 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] in 2006 and Rai SK et al . [ 20 ] in 2015, refractive error varies with ethnicity. Various components like nutrition, lifestyle, and hereditary might be involved in contributing to the rise of refractive errors.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the commonest refractive error among school children was astigmatism , followed by myopia (26%) and then hypermetropia (19%). 28 Pavithra et al in Bangalore, 21 Sethi S et al among school children of Ahmedabad, 22 and S Matta et al among the adolescents attending outpatient department of ophthalmology in New Delhi, 23 concluded that myopia was the most common refractive error among school children followed by astigmatism and hypermetropia. A study conducted by Medi K et al in Kampala district showed that the commonest refractive error was astigmatism (52%), followed by hypermetropia (37%) children and myopia (11%).…”
Section: Discussionmentioning
confidence: 99%